Spermidine in dementia: Relation to age and memory performance - Pekar, Thomas; Wendzel, Aribert; Flak, Walter; Kremer, Alexandra; Pauschenwein-Frantsich, Susanne; Gschaider, Anna; Wantke, Felix; Jarisch, Reinhart (Wiener Klinische Wochenschrift, 2020)
Summary Previous studies have highlighted that spermidine has the ability to trigger the important process of dissolving amyloid-beta plaques by autophagy. This manuscript focuses on the correlation of serum spermidine levels between age and between performance in mini-mental state examinations. It will serve as a premise for an ongoing multicentric placebo-controlled study, which focuses on the effect of oral spermidine supplementation on memory performance. Memory tests were carried out on 80 subjects aged 60–96 years old in 6 nursing homes in Styria. Blood samples were taken for the determination of spermidine concentration. The results showed a significant correlation between the spermidine concentration and the mini-mental state examination score ( p = 0.025). On the basis of the dependence demonstrated it can be concluded that spermidine might be suitable as a biomarker for the diagnosis of neurocognitive changes (senile dementia or Alzheimer’s disease).